Shaping Future Educators: The Role of Invertebrate Dissections, Handling, and Consumption in Influencing Biology Teachers' Attitudes - Iľko, Ivan; Maruniaková, Alexandra; Peterková, Viera (Journal of Social and Scientific Education, 2025)
This study examines the pedagogical impact of dissection, handling, and consumption of invertebrates on the attitudes of prospective biology teachers toward these organisms. The research aimed to evaluate how experiential teaching methods influence emotional responses, willingness to protect, and openness to consuming invertebrates. The research sample consisted of 40 third-year female students enrolled in a biology teacher education program at a Slovak pedagogical university. Over one semester, participants completed six dissections and participated in four tastings of edible invertebrates. Data were collected using a standardized 52-item questionnaire administered before and after the intervention. The Wilcoxon matched-pairs test was employed for statistical analysis. The results revealed that dissection alone did not significantly influence students' attitudes toward invertebrate conservation; however, a statistically significant decrease in aversion was observed, particularly among participants who had initially expressed low willingness to consume these organisms. Overall openness to consumption increased markedly, and a relationship was identified between prior openness and a subsequently stronger conservation attitude. These findings suggest that practical engagement with biological material, particularly when combined with unconventional approaches such as consumption, may reduce affective barriers and foster a more positive perception of invertebrates. From an educational perspective, such experiential approaches may enhance the professional confidence of future biology teachers when working with these organisms and simultaneously contribute to the development of ethically grounded and sensitive biodiversity education. Further research is recommended on a more diverse sample, incorporating qualitative methods to gain deeper insight into students’ subjective experiences.